2016
DOI: 10.1128/aem.01063-16
|View full text |Cite
|
Sign up to set email alerts
|

Novel acsF Gene Primers Revealed a Diverse Phototrophic Bacterial Population, Including Gemmatimonadetes, in Lake Taihu (China)

Abstract: Anoxygenic phototrophs represent an environmentally important and phylogenetically diverse group of organisms. They harvest light using bacteriochlorophyll-containing reaction centers. Recently, a novel phototrophic bacterium, Gemmatimonas phototrophica, belonging to a rarely studied phylum, Gemmatimonadetes, was isolated from a freshwater lake in the Gobi Desert. To obtain more information about the environmental distribution of phototrophic Gemmatimonadetes, we collected microbial samples from the water colu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…In general, APB communities in both lakes were dominated by Alpha- and Betaproteobacteria (Fig. 3), which is consistent with previous reports 16,26,27,44,45 . However, these two lakes differed largely at the OTU level, with only less than 10% of the OTUs shared between them (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In general, APB communities in both lakes were dominated by Alpha- and Betaproteobacteria (Fig. 3), which is consistent with previous reports 16,26,27,44,45 . However, these two lakes differed largely at the OTU level, with only less than 10% of the OTUs shared between them (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The first cultured Chloroflexi were thermophilic species originating from various thermal springs 7,49,50 . In recent years, several studies registered puf M sequences belonging to phototrophic Chloroflexi in various freshwater habitats 16,22,37 . Here, we provide further evidence that freshwater phototrophic Chloroflexi were not only present, but also highly active in photosynthetic gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic analysis showed that the M. oxyfera -like sequences recovered were 90–97% identical to the 16S rRNA gene of Candidatus Methylomirabilis oxyfera [10]. These sequences were closely related (>96% identical) to the M. oxyfera -like sequences reported in enrichment cultures [52], lake sediments [23, 58, 59], and paddy soil [27] (Fig. 5).…”
Section: Resultsmentioning
confidence: 88%
“…Polynucleobacter duraquae is also most often found in fresh water samples (and is free-living unlike many host-associated Polynucleobacter species) (Hahn et al, 2016). Similarly, the OTUs annotated as Comamonadaceae MG_12 (placed as within the genera Acidovorax or Limnohabitans) and Bordetella_1 did not correspond to any well characterized bacterial species, but have previously been identified or isolated as unknown bacteria (100% similar) from numerous samples deriving from fresh water (Shaw et al, 2008;Mueller-Spitz et al, 2009;Wu et al, 2012;Elser et al, 2014;Balmonte et al, 2016;Huang et al, 2016) and were also only detected in laboratory samples.…”
Section: Real-world Data Testing: International Space Station Data Setmentioning
confidence: 99%